Efficient Generation of Plasmacytoid Dendritic Cell from Common Lymphoid Progenitors by Flt3 Ligand. - Yi-Ling Chen; Shiun Chang; Ting-Ting Chen; Chien-Kuo Lee (PLoS ONE, 2015)
Dendritic cells (DCs), including conventional DCs (cDCs) and plasmacytoid DCs (pDCs) are critical for initiating and controlling the immune response. However, study of DC, particularly pDC, function is hampered by their low frequency in lymphoid organs, and existing methods for in vitro DC generation preferentially favor the production of cDCs over pDCs. Here, we demonstrated that pDCs could be efficiently generated in vitro from common lymphoid progenitors (CLPs) using Flt3 ligand (FL) in three different culture systems, namely feeder-free, BM-feeder and AC-6-feeder. This was in stark contrast to common DC progenitors (CDPs), in which cDCs were prominently generated under the same conditions. Moreover, the efficiency and function of pDCs generated from these three systems varied. While AC-6 system showed the greatest ability to support pDC development from CLPs, BM-feeder system was able to develop pDCs with better functionality. pDCs could also be expanded in vivo using hydrodynamic gene transfer of FL, which was further enhanced by the combined treatment of FL and IFN-α. Interestingly, IFN-α selectively promoted the proliferation of CLPs and not CDPs, which might contribute to enhanced pDC development. Together, we have defined conditions for in vitro and in vivo generation of pDCs, which may be useful for investigating the biology of pDCs.